(untitled) (Research, Society and Development, 2021)
Introduction: The American College of Obstetricians and Gynecologists (ACOG) in 2017 recommended that this section of the umbilical cord should be done in 30 to 60 seconds for premature babies, which is scientifically based on reducing possible complications related to the premature. Objective: To highlight the importance and benefits of late clamping of the umbilical cord. Method: This is an integrative literature review, carried out in LILACS databases; BDENF; MEDLINE; SciELO. Results: The cut performed after 60 seconds shows greater blood transfer to the newborn (NB). However, they point out that some professionals wait for the cord to stop pulsating to perform the clamping, which results in greater efficiency in practice. Conclusion: The performance of this practice allows numerous benefits for the baby during delivery and in early childhood, mainly preventing anemia in this age group.